Storytelling in Presentations - Lindsell-Roberts, Sheryl, 1943- (Hoboken, NJ : John Wiley & Sons, Inc, 2024)
"Storytelling in Presentations For Dummies shows you how to develop and deliver a presentation through storytelling, keeping audience interested, and most importantly, making them heroes that take action towards change. You'll learn how to cull stories from your own experiences, and before you know it, you'll have more stories than Aesop has fables. You'll learn about the latest presentation software, so you can integrate visuals into your presentations and avoid the dreaded "Death by PowerPoint." You'll also learn how to deal with challenging on-the-spot situations, deliver investor pitches and executive briefs, and present a paper at a conference. Additionally, find out how to deliver someone else's content and make it your own. This book will help you level up anywhere you need to present information by mastering the art of savvy presentations--the most effective business communications tools of our time"--
Introduction -- Martians, stories, and heroes -- Nuts 'n' bolts -- Adding flourishes -- It's showtime -- Specialized presentations -- The part of tens.
Includes index.
"Create engaging stories to capitvate audiences; Turn slides from drab to fab; Storyboard to prepare the show and tell"--Cover.
Keywords: Business presentations; Public speaking; Storytelling